Pearls of Jaina Wisdom: A Selection of Inspiring Aphorisms from the Jaina Scriptures - Thottakara, Augustine (Journal of Dharma, 1999)
Dulichand Jain, Pearls of Jaina Wisdom. A Selection of Inspiring Aphorisms from the Jaina Scriptures, Varanasi: Parshvanath Vidyapith & Madras: Research Foundation for Jainology, 1997, pp.xxxxii+328; Rs. 120.00 (ISBN 81-86715-18-5).